2019
DOI: 10.1080/14017431.2019.1612087
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) is not associated with venous thromboembolism risk

Abstract: Objectives. Evidence from case-control studies as well as meta-analyses of these study designs suggest elevated lipoprotein(a) [Lp(a)] to be associated with an increased risk of venous thromboembolism (VTE). Prospective evidence on the association is limited, uncertain, and could be attributed to regression dilution bias. We aimed to assess the prospective association of Lp(a) with risk of VTE and correct for regression dilution. Design. We related plasma Lp(a) concentrations to the incidence of VTE in 2,180 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Several case-control studies have shown increased VTE risk with elevated Lp(a) concentrations [79][80][81]. On the contrary, a population-based prospective study in 2180 middle-aged men without a history of VTE at the study entry showed no evidence of an association of circulating Lp(a) with the risk of VTE [82]. These results are similar to previous prospective studies in different populations [83][84][85][86].…”
Section: Pcsk9 Monoclonal Antibodies and Coagulation And Fibrinolytic...supporting
confidence: 86%
“…Several case-control studies have shown increased VTE risk with elevated Lp(a) concentrations [79][80][81]. On the contrary, a population-based prospective study in 2180 middle-aged men without a history of VTE at the study entry showed no evidence of an association of circulating Lp(a) with the risk of VTE [82]. These results are similar to previous prospective studies in different populations [83][84][85][86].…”
Section: Pcsk9 Monoclonal Antibodies and Coagulation And Fibrinolytic...supporting
confidence: 86%
“…However, the association between Lp(a) and VTE is not yet well clarified. While a meta-analysis and several other studies show a significant association between high levels of Lp(a) and increased risk of VTE in adults [ 139 , 140 , 141 , 142 ], other studies did not confirm this association [ 143 , 144 , 145 ].…”
Section: Hypofibrinolysis Associated With Onjmentioning
confidence: 91%
“…The VTE prediction model were established with purpose of making accurate assessment and diagnosis of VTE in the first time and avoiding adulterating human factors as much as possible. We know that there is a lot of VTE-related information in the electronic medical record system [27,[33][34][35][39][40][41], and such information needs to be further explored and fully utilized in the clinical VTE warning. The VTE risk warning model made full use of Caprini risk assessment scale, which was widely used in clinical medicine and surgery, with the important clinical symptoms and signs of VTE patients and laboratory examination indicators, to carry out comprehensive and multi-dimensional warning and achieve higher prediction efficiency.…”
Section: Clinical Significance Of Vte Early Warning Modelmentioning
confidence: 99%